Professional Service Utilisation among Patients with Severe Mental Disorders - Caron Jean; Bamvita Jean-Marie; Grenier Guy; Fleury Marie-Josée (BMC, 2010)
Abstract Background Generally, patients with serious mental disorders (SMD) are frequent users of services who generate high care-related costs. Current reforms aim to increase service integration and primary care for improved patient care and health-care efficiency. This article identifies and compares variables associated with the use by patients with SMD of services offered by psychiatrists, case managers, and general practitioners (GPs). It also compares frequent and infrequent service use. Method One hundred forty patients with SMD from five regions in Quebec, Canada, were interviewed on their use of services in the previous year. Patients were also required to complete a questionnaire on needs-assessment. In addition, data were collected from clinical records. Descriptive, bivariate, and multivariate analyses were conducted. Results Most patients used services from psychiatrists and case managers, but no more than half consulted GPs. Most patients were followed at least by two professionals, chiefly psychiatrists and case managers. Care access, continuity of care, and total help received were the most important variables associated with the different types of professional consultation. These variables were also associated with frequent use of professional service, as compared with infrequent service use. In all, enabling factors rather than need factors were the core predictors of frequency of service utilisation by patients with SMD. Conclusion This study reveals that health care system organisation and professional practice - rather than patient need profiles - are the core predictors of professional consultation by patients with SMD. The homogeneity of our study population, i.e. mainly users with schizophrenia, recently discharged from hospital, may partly account for these results. Our findings also underscored the limited involvement of GPs in this patient population's care. As comorbidity is often associated with serious mental disorders, closer follow-up by GPs is needed. Globally, more effort should be directed at increasing shared-care initiatives, which would enhance coordination among psychiatrists, GPs, and psychosocial teams (including case managers). Finally, there is a need to increase awareness among health care providers, especially GPs, of the level of care required by patients with disabling and serious mental disorders.